2012
DOI: 10.1111/j.1551-2916.2011.05064.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transitions and Microwave Dielectric Properties of Ba2−2xSr2xSmSbO6 Double Perovskites

Abstract: Structures and microwave dielectric properties of Ba2−2xSr2xSmSbO6 (x = 0–1) ceramics were studied in this article. The phase transitions were analyzed using X‐ray powder diffraction, transmission electron microscopy, and Raman spectroscopy. All structures are proved to be ordered double perovskites, and a series of composition‐induced phase transitions are confirmed in the Ba2−2xSr2xSmSbO6 system via the sequence: Fm‐3m → I2/m → P21/n. Dielectric properties of the ceramics were measured at microwave frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The structural studies of A 2 B′B″O 6 (A = Ba, Sr, Ca; B′ = lanthanide, Mg, Cr, Bi; B″ = Nb, Ta, Sb, W) indicated that phase transitions were ascribed to the tilting of B′O 6 /B″O 6 . In the Ba 2-2x Sr 2x SmSbO 6 system, phase transitions of Fm3m, I 2 /m, and P2 1 /n were observed and the τ f value shifted from +25 to -50 ppm/ [473]. Effect of non ℃ stoichiometry Ba 1+x (MgW) 1/2 O 3 , Ba(Mg 1+y W) 1/2 O 3 , and Ba(MgW 1+z ) 1/2 O 3 and the sintering temperature on microwave dielectric properties was systematically investigated by Wu and Bian [474] and Chen et al [475], respectively.…”
Section: A 2 B′b″o 6 Formulamentioning
confidence: 97%
“…The structural studies of A 2 B′B″O 6 (A = Ba, Sr, Ca; B′ = lanthanide, Mg, Cr, Bi; B″ = Nb, Ta, Sb, W) indicated that phase transitions were ascribed to the tilting of B′O 6 /B″O 6 . In the Ba 2-2x Sr 2x SmSbO 6 system, phase transitions of Fm3m, I 2 /m, and P2 1 /n were observed and the τ f value shifted from +25 to -50 ppm/ [473]. Effect of non ℃ stoichiometry Ba 1+x (MgW) 1/2 O 3 , Ba(Mg 1+y W) 1/2 O 3 , and Ba(MgW 1+z ) 1/2 O 3 and the sintering temperature on microwave dielectric properties was systematically investigated by Wu and Bian [474] and Chen et al [475], respectively.…”
Section: A 2 B′b″o 6 Formulamentioning
confidence: 97%
“…The angle θ is the phase change on reflection, and by knowing R ω c and θ ω c , n and R can be calculated from (15) and (16) [107]. The value of θ at any frequency ω c is not isolated, while it is directly interrelated with the reflection spectra by the integral transform.…”
Section: K-k Analysismentioning
confidence: 99%
“…1, pp. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] This is an open access article published by the IET under the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0/) the complex nature of the atoms in the B-site promotes the splitting of the vibrational modes, leading to a more complicated IR spectrum.…”
Section: Effect Of Processing Conditions On Fir Phonon Modes Of Mwdcsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard DPOs having rare-earth and d 0 transition metal as B-site and alkaline earth element as A-site cation are widely studied for microwave resonators, filters etc. [5][6][7][8][9][10]. Among them much attention has been paid to Ba 2 LnMO 6 and Sr 2 LnMO 6 [Ln: lanthanides, M: Nb, Ta] families [5,6].…”
Section: Introductionmentioning
confidence: 99%